Murine Model of Interstitial Cytomegalovirus Pneumonia in Syngeneic Bone Marrow Transplantation: Persistence of Protective Pulmonary CD8-T-Cell Infiltrates after Clearance of Acute Infection - Podlech, Jürgen (American Society for Microbiology, 2000)
Interstitial pneumonia (IP) is a severe organ manifestation of cytomegalovirus (CMV) disease in the immunocompromised host, in particular in recipients of bone marrow transplantation (BMT). Diagnostic criteria for the definition of CMV-IP include clinical evidence of pneumonia together with CMV detected in bronchoalveolar lavage or lung biopsy. We have used the model of syngeneic BMT and simultaneous infection of BALB/c mice with murine CMV for studying the pathogenesis of CMV-IP by controlled longitudinal analysis. A disseminated cytopathic infection of the lungs with fatal outcome was observed only when reconstituting CD8 T cells were depleted. Neither CD8 nor CD4 T cells mediated an immunopathogenesis of acute CMV-IP. By contrast, after efficient hematolymphopoietic reconstitution, viral replication in the lungs was moderate and focal. The histopathological picture was dominated by preferential infiltration of CD8 T cells confining viral replication to inflammatory foci. Notably, after clearance of acute infection, CD62L(lo) and CD62L(hi) subsets of CD44(+) memory CD8 T cells were found to persist in lung tissue. One can thus operationally distinguish an early CMV-positive IP (phase 1) and a late CMV-negative IP (phase 2). According to the definition, phase 2 histopathology would not be diagnosed as a CMV-IP and could instead be misinterpreted as a CMV-induced immunopathology. We document here that phase 1 as well as phase 2 pulmonary CD8 T cells are capable of exerting effector functions and are effectual in protecting against productive infection. We propose that antiviral “stand-by” memory-effector T cells persist in the lungs to prevent virus recurrence from latency.